The relationship between mental workload and nurse stress levels in hospitals - Zahid Fikri; Adelia Bellarifanda; Sunardi Sunardi; Muhammad Rosyidul 'Ibad; Khikmatul Mu'jizah (PAGEPress Publications, 2023)
High mental workload implies significant mental resources and can lead to increased cognitive stress and fatigue. Nurses have the responsibility of managing a wide range of nursing care tasks, which frequently involve addressing anxiety, handling patient complaints, and managing patient defense mechanisms, all of which can lead to increased stress levels. This study aimed to identify the relationship between mental workload and the stress level of nurses in the Hospital Malang City. The research utilized a cross-sectional study design. The sampling technique employed was Total Sampling, involving 96 inpatient nurses at the hospital. Data collection involved the use of two questionnaires: the National Aeronautics and Space Administration Task Load Index (NASA-TLX) and the Perceived Stress Scale (PSS-10). Data analysis in this study was conducted using Pearson Correlation. The results indicated a positive relationship between mental workload and nurses' stress levels, supported by a significant p-value of 0.002 and a correlation coefficient of 0.312. A high mental workload can impact the level of job-related stress experienced by nurses. Effective stress management skills can help individuals mitigate this impact.